Impact of somatic copy number alterations on the glioblastoma miRNome: miR‐4484 is a genomically deleted tumour suppressor. Issue 8 (24th May 2017) - Nawaz, Zahid; Patil, Vikas; Thinagararjan, Sivaarumugam; Rao, Soumya A.; Hegde, Alangar S.; Arivazhagan, Arimappamagan; Santosh, Vani; Somasundaram, Kumaravel
Abstract : Glioblastoma (GBM) is the most frequent and most malignant primary brain tumour in adults. GBMs have a unique landscape of somatic copy number alterations (SCNAs), with the concomitant appearance of numerous driver amplifications and deletions. Here, we examined the genomic regions harbouring SCNAs and their impact on the GBM miRNome. We found that 40% of SCNA events covering 70–88% of the genomically altered regions, as identified by GISTIC and RAE algorithms, carried miRNA genes. Of 1426 annotated mature miRNAs analysed, ~ 14% ( n  = 198) were mapped to such fragile loci. Further, we identified an intragenic miRNA, miR‐4484 located on chromosome‐10, as a deleted and downregulated miRNA in GBM. miR‐4484 exhibited a strong positive correlation with the expression of its host gene uroporphyrinogen III synthase ( UROS ), thereby indicating that the loss of miR‐4484 is a codeletion event in GBM. Overexpression of miR‐4484 reduced the colony‐forming ability and suppressed the migratory capacity of glioma cells. Analysis of the RNA‐seq‐derived transcriptome upon exogenous miR‐4484 overexpression in conjunction with an integrative bioinformatics approach revealed several putative targets of miR‐4484. Unbiased functional enrichment of these targets through DAVID identified a cohort of important gene ontology terms, which possibly explain the functional role of miR‐4484 in gliomagenesis. Selected targets were validated and, importantly, were found to be upregulated in GBM. In brief, our study identified a panel of miRNAs that are likely to be regulated by genomic deletions and amplifications. Further, miR‐4484 was found to be deleted and acts as a tumour suppressor miRNA in GBM. Abstract : Glioblastomas have a unique landscape of somatic copy number alterations (CNAs). These fragile genomic loci frequently harbor miRNAs. We found that 40% of CNA events in glioblastoma harbored miRNAs, covering 70‐88 % of the aberrant genome. Also, about 14% of the total miRNAs localize to such fragile loci, underscoring the importance of CNAs as a cause of miRNA misregulation in glioblastoma.